PERILAKU HIDUP BERSIH DAN SEHAT PADA ANAK SEKOLAH DASAR - Akbar, Fajar; Adiningsih, Ridhayani; Islam, Fahrul; DN, Nurhidayah (Poltekkes Kemenkes Bengkulu, 2023)
Abstract School children are one of the targets for Clean and Healthy Behavior (PHBS) in educational institutions and need to get attention besides the large population of school-age children in a community. The role of behaviour on the level of health, then promoting a healthy lifestyle in the elementary school students is very necessary. PHBS is very important to appyin everyday life, especially elementary school-age children. This study aims to determine the description of clean and healthy living behaviour in elementary schools. This research method is descriptive research. The research location was carried out at Bone-Bone Pantai Elementary School, Bambu Village, Mamuju District. Research time in June 2021. The samples in thi study were 27 students in grade 4, 30 stundents in grade 5 and 30 stundents in grade 6. The research instrument was to use a questionnaire containing questions and stationery and presenting data in the form of tables and narratives. Based on the results of this study, it showed that elementary school children had a high level of knowledge about good PHBS 94,3% and elementary school students actions that fulfilled the requirements 91,1 %. Suggestions from this study are for students to maintain habits of clean and healthy living behavior. Keywords : behavior, PHBS, elementary school students